2008
DOI: 10.1002/yea.1591
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of non‐translatable mRNA silences. The transcription of Ty1 retrotransposons in S. cerevisiae via functional inactivation of the nuclear cap‐binding complex and subsequent hyperstimulation of the TORC1 pathway

Abstract: Co-suppression is high gene copy number-triggered homology-dependent gene silencing, and co-suppression may have evolved in eukaryotes to counter invasive molecular parasites, such as viruses and transposons. We previously reported 'Ty1 transcriptional co-suppression' -high Ty1 copy number-triggered transient transcriptional silencing of Ty1 retrotransposons in S. cerevisiae. We report here that this phenomenon is unlikely to be homology-dependent, despite the copy number dependence. The Ty1 mRNA is an extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…These transcripts are subsequently degraded through a process called non-sense mediated decay [57]. How increased abundance of truncated transcripts influence cellular response is not exactly clear, however in one such study in an unrelated system, it was shown that non-sense mediated decay cramps the nuclear cap binding protein (NCBP) in an inactive form thereby influencing the cytosolic export of newly formed transcripts [58]. It will be interesting to see whether similar mechanisms are operational in higher eukaryotes as well.…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts are subsequently degraded through a process called non-sense mediated decay [57]. How increased abundance of truncated transcripts influence cellular response is not exactly clear, however in one such study in an unrelated system, it was shown that non-sense mediated decay cramps the nuclear cap binding protein (NCBP) in an inactive form thereby influencing the cytosolic export of newly formed transcripts [58]. It will be interesting to see whether similar mechanisms are operational in higher eukaryotes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we had shown that reporter gene expression driven by the BARE LTR is dependent on the presence of TATA2 and not TATA1 [19,31], strongly suggesting that all translated BARE proteins are derived from TATA2. Capping and polyadenylation have not been well investigated for LTR retrotransposons; Ty1 and copia of Superfamily Copia are translated from capped RNA [32,33] while Idefix of superfamily Gypsy exploits both cap-dependent and independent mechanisms [34]. Retroviruses, which are likely derived from Gypsy retrotransposons [3], produce capped transcripts but appear to exploit both cap-dependent and ‑independent translation [35].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that only the tap42‐106 defect in Ty1 transcriptional silencing is not upstream of CBC. We have previously shown that plasmids expressing high levels of non‐translatable mRNAs are potent at silencing Ty1 transcription (Wu and Jiang, 2008), and we refer to plasmids such as YEp[LEU2]:Ty1(1–479) and YEp[LEU2]:pPGK1 as ‘super‐initiators’. Importantly, these plasmids fail to silence Ty1 transcription in tap42‐106 cells (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…A number of genetic observations support that both the CBC and the rapamycin‐sensitive TORC1 pathway are involved in mediating Ty1 transcriptional silencing (Wu and Jiang, 2008). First, a non‐lethal concentration of rapamycin eliminates Ty1 transcriptional silencing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation